(untitled) (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2026)
This study explores the linguistic features of Indoglish, a contact variety of English with the Indonesian language and culture, focusing on its use in digital and social media. Grounded in a language contact perspective, this study argues that speaking English nuanced by Indonesian linguistic structures is a natural and legitimate practice that reflects linguistic identity rather than linguistic deficiency. Using a qualitative descriptive approach, data in this study were collected from 5 TikTok videos produced by an Indonesian content creator and analyzed to discuss the linguistic features of Indoglish, particularly phonological, morpho-syntactic, and pragmatic features. The findings demonstrate that Indoglish utilizes distinctive linguistic features with standard English. At the phonological level, Indoglish shows systematic pronunciation patterns influenced by Indonesian, such as TH-replacement, deletion of final plosives, addition of /r/ sound, final devoicing, and vowel adjustment. At the morpho-syntactic level, Indoglish employs the use of copula omission, reduplication, syntactic transfer, and morphological transfer, reflecting the influence of Indonesian structures. Additionally, Indoglish at the pragmatic level displays the use of sentence-final particles, discourse markers, tag questions, address terms, code-switching, stance markers, and self-repair. These features indicate that Indoglish represents the active role of Indonesian as the mother tongue and national language in speaking English by Indonesians. Furthermore, this study argues that Indoglish should be understood as an expression of linguistic identity and creativity rooted in Indonesian rather than viewing such forms as errors. This study highlights the importance of recognizing Indonesian influence as a valuable linguistic resource in contemporary English use. This perspective is particularly relevant for English education students, as it encourages confidence and reduces anxiety in using English influenced by their mother tongue.